Upload File Security on the Server Using LSB and Hill Cipher - Lekso Budi Handoko; Chaerul Umam; Adelia Syifa Anindita (Journal of Applied Intelligent System, 2019)
The rapid development of technology not only has a positive impact, but also can have a negative impact such as the development of cyber crime that can cause messages to be unsafe. Message security can be protected using cryptography to convert messages into secret passwords. Steganography is a technique of hiding messages by inserting messages into images that are used to increase message security. In this study, it discusses a combination of hill cipher and LSB algorithms to secure messages. The message used is a 3-bit grayscale image for steganography and text messages with 32, 64 and 128 characters for cryptography. The measuring instruments used in this study are MSE, PSNR, Entropy and travel time (CPU time). Test results prove an increase in security without too damaging the image. This is evidenced by the results of the MSE trial which has a value far below the value 1, the PSNR is> 65 dB with a range of entropy values of 5 to 7, and travel times are almost the same.